Implementation of Ice Breaking in Increasing Student’s Spirit of Learning: (Case Study of STIT Al Hikmah Tebing Tinggi Private Students) - Khodijah, Siti (LPPPIPublishing, 2023)
The application of interesting and unique ice breaking can be a solution to overcome student boredom and saturation in learning activities. Exciting and fun ice breaking activities can strengthen connections, build concentration, improve communication, and create a warmer and friendlier atmosphere. Ice Breaking activities are generally used in several parts of the activity. One of them is when opening a lecture. The implementation of ice breaking in learning to reduce student learning boredom was carried out in the second semester of the Early Childhood Islamic Education Study Program, Al Hikmah Tebing Tinggi Tarbiyah Science College. Based on the research results, it appears that there is an effect of implementing ice breaking in reducing boredom and increasing student enthusiasm for learning. The decrease in learning boredom from the high to low category was inseparable from the influence of the implementation of ice breaking which was carried out over twelve meetings and saw a shift in students' attitudes from what previously looked tense to being cheerful. Ice breaking can foster interest in learning, make the atmosphere more comfortable and can increase student cohesiveness in class and during the lecture process. This research aims to explain the application of ice breaking in student learning activities in class. In this research, qualitative methods and literature study were used. The data obtained is collected, analyzed, and conclusions are drawn in the implementation of learning each week so that it can be seen and compared whether learning uses ice breaking or not.